2019
DOI: 10.1186/s13104-019-4218-z
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D3 supplementation and treatment outcomes in patients with depression (D3-vit-dep)

Abstract: Objective To examine whether vitamin D supplementation in patients with depression would result in a reduction in Hamilton D-17 depression score (primary outcome) at 3 and 6 months compared to controls and to explore the correlations between serum vitamin D and symptoms of depression, wellbeing, systolic blood pressure, and waist circumference. In this outpatient multicentre study conducted between 2010 and 2013, patients, 18–65 years old, diagnosed with mild to severe depression were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 18 publications
1
34
0
6
Order By: Relevance
“…Of the clinical trials present in this review, three found improvements with the use of vitamin D supplementation in depression symptoms: Alavi et al 11 , Omidian et al 13 , and Zheng et al 14 Three other studies found no improvement: Hansen et al 9 , Marsh et al 10 , and Kjaergaard et al 12 Hansen et al 9 In the study by Marsh et al 10 , the participants were allocated in a 1:1 ratio. The participants received 5,000 IU vitamin D3 (cholecalciferol) capsules daily or placebo for 12 weeks.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Of the clinical trials present in this review, three found improvements with the use of vitamin D supplementation in depression symptoms: Alavi et al 11 , Omidian et al 13 , and Zheng et al 14 Three other studies found no improvement: Hansen et al 9 , Marsh et al 10 , and Kjaergaard et al 12 Hansen et al 9 In the study by Marsh et al 10 , the participants were allocated in a 1:1 ratio. The participants received 5,000 IU vitamin D3 (cholecalciferol) capsules daily or placebo for 12 weeks.…”
Section: Discussionmentioning
confidence: 90%
“…The clinical trials showed a homogeneous methodological quality based on the risk of bias assessment using the Cochrane tool (Table 1) [9][10][11][12][13][14] . Random generation and allocation concealment were adequately reported in 83.35% (5/6) of the studies; blinding of participants and professionals was reported in 100% (6/6) with a low risk of bias; blinding of the outcome evaluators was reported in 50% (3/6) with a low risk of bias; incomplete outcomes were reported in 66.66% (4/6) with a low risk of bias; selective outcome reporting was reported in 100% (6/6) with uncertain risk of bias; and other sources of bias were reported in 16.6% (1/6) with low risk of bias.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A manutenção dos seus níveis adequados no paciente com depressão, é possivelmente capaz de reduzir os sintomas depressivos e influenciar em um bom prognóstico (FOCKER et al, 2018). Um estudo multicêntrico ambulatorial, duplo-cego e randomizado, realizado entre 2010 e 2013 envolvendo pacientes com diagnóstico de depressão, de graus leve a grave, mostrou que não houve melhora dos sintomas depressivos com a suplementação de vitamina D (HANSEN et al, 2019). Neste estudo o tratamento padrão se mostrou eficaz, sendo provavelmente a suplementação da vitamina um fator sem grandes atuações.…”
Section: Vitamina Dunclassified
“…Essas diferenças obtidas nas investigações podem ser atribuídas às limitações de cada estudo. De forma semelhante,Hansen et al (2019) constataram que a intervenção não reduziu os valores da escala utilizada para avaliar os sintomas depressivos na população estudada. Os autores argumentam que embora todos os participantes tenham tido diagnóstico de depressão, o tamanho da população era muito pequeno para determinar se a vitamina D é útil em uma população recebendo tratamento padrão eficaz para a depressão.Como observado na maioria dos estudos científicos envolvendo a vitamina D, as investigações tiverem como finalidade avaliar efeitos da suplementação com este micronutriente.…”
unclassified